Distinct Physiological Roles of Fructokinase Isozymes Revealed by Gene-Specific Suppression of Frk1 and Frk2 Expression in Tomato - Odanaka, Saori (American Society of Plant Physiologists, 2002)
There are two divergent fructokinase isozymes, Frk1 and Frk2 in tomato (Lycopersicon esculentum Mill.) plants. To investigate the physiological functions of each isozyme, the expression of each fructokinase mRNA was independently suppressed in transgenic tomato plants, and the respective phenotypes were evaluated. Suppression of Frk1 expression resulted in delayed flowering at the first inflorescence. Suppression of Frk2 did not effect flowering time but resulted in growth inhibition of stems and roots, reduction of flower and fruit number, and reduction of seed number per fruit. Localization of Frk1 and Frk2 mRNA accumulation by in situ hybridization in wild-type tomato fruit tissue indicated that Frk2 is expressed specifically in early tomato seed development. Fruit hexose and starch content were not effected by the suppression of either Frk gene alone. The results collectively indicate that flowering time is specifically promoted by Frk1 and that Frk2 plays specific roles in contributing to stem and root growth and to seed development. Because Frk1 and Frk2 gene expression was suppressed individually in transgenic plants, other significant metabolic roles of fructokinases may not have been observed if Frk1 and Frk2 play, at least partially, redundant metabolic roles.